K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 10 2017

\(Ix-2I+x+3\)

a, Thay x=-1 vào biểu thức , ta có :

/-1-2/+(-1)+3=/-3/-1+3

                     =3-1+3

                     =5

 

a: x>-3/5 nên x+3/5>0

x<1/7 nên x-1/7<0

A=1/7-x-(x+3/5)+4/5

=1/7-2x-3/5+4/5

=-2x+12/35

b: \(B=\left|-x+\dfrac{1}{7}\right|+\left|-x-\dfrac{3}{5}\right|-\dfrac{2}{6}\)

\(=\left|x-\dfrac{1}{7}\right|+\left|x+\dfrac{3}{5}\right|-\dfrac{1}{3}\)

-3/5<x<1/7

nên x-1/7<0; x+3/5>0

\(B=\dfrac{1}{7}-x+x+\dfrac{3}{5}-\dfrac{1}{3}=\dfrac{43}{105}\)

c: \(C=\left|\dfrac{11}{5}-x\right|+\left|x-\dfrac{1}{5}\right|+\dfrac{41}{5}\)

\(=\left|x-\dfrac{11}{5}\right|+\left|x-\dfrac{1}{5}\right|+\dfrac{41}{5}\)

Nếu 1/5<x<11/5 nên x-1/5>0; x-11/5<0

\(C=\dfrac{11}{5}-x+x-\dfrac{1}{5}+\dfrac{41}{5}=\dfrac{51}{5}\)